Medical Rehabilitation Impact Towards Dynamic Balance in Lateral Ankle Sprain Patients - Jonathan Salim; Nana Novia Jayadi; Mirna Phandu; Moses Rizky Haryanto (Universitas Airlangga, 2023)
Background: Lateral ankle sprain (LAS) is one of the most prevalent and recurring injuries occurring during physical activities, especially sports. The resulting morbidity forces individuals to limit or change their physical activities. Medical rehabilitation can prevent recurrent injuries by restoring dynamic balance deficits. Previous studies have shown contradictory results. We investigated the effect of medical rehabilitation on dynamic balance in patients with LAS.Methods: This was a numerical, analytical study with a prospective cohort design. Two groups, consisting of 13 LAS subjects each, were purposively chosen. Only the former participated in the three sessions of the rehabilitation program. The modified star excursion balance test was performed initially and three weeks later. Normalized composite scores were recorded in Microsoft Excel and statistically analyzed using SPSS 24 with a 5% significance level.Results: LAS was commonly found in males (57.69%), with an average age of 20.62 ± 6.24 years old, on the dominant foot side (57.69%). Both groups were matched for age (p = 0.292), sex (p = 0.247), and dominant injured foot (p = 0.193). The rehabilitation group presented a greater increase in normalized composite score than the control (∆ = 3.10 ± 4.71 vs. 2.04 ± 7.05, p = 0.654).Conclusion: Dynamic balance increased more in the rehabilitation group than in the control group, but the difference was insignificant. Medical rehabilitation should not be mandatory but optional for patients with LAS with limited resource access. Nevertheless, rehabilitation should be continued for other important aspects of treatment.